Features of Distance Learning in the University Education System of Kazakhstan - Iskaliyeva, Ainagul; Issaliyeva, Aizada; Kurmanova, Bibiqul; Yermekova, Assemgul; Magauova, Aigul; Bapiyev, Ideyat (Journal of Ecohumanism, 2024)
The purpose of this work is to describe the modeling method and the possibility of developing a relatively inexpensive but effective educational platform using the example of an existing distance learning information system. The method of the created system is based on a special approach to the use of modern digital tools that allows one to automate the learning process at a distance. To create an information system for distance learning, a number of requirements and performance criteria were taken into account, which were determined on the basis of an expert analysis of several other similar well-known educational platforms. To develop the software component of the distance learning system, the choice was made on the scripting programming language Hypertext Preprocessor (PHP). The validity of the choice of programming language lies in the fact that, at present, this language is supported by the vast majority of organizations providing professional hosting services. PHP is an easy-to-use language, has a wide range of functionality, is flexible in terms of cross-platforms and is one of the leading languages used to create dynamic websites. The developed system, in full, serves as a good example of demonstrating the main possibilities of using modern information technologies in the field of distance learning. The approach of the received distance learning system at the university has practically proven the effectiveness of this system in the educational process. The users of the information system noted convenient access to the necessary content, ease of analysis of the learning process, and the user-friendly interface of the platform. From a technical standpoint, the introduction of this system into the educational process of a higher educational institution or organization will not incur high economic costs.